Assessment of the development of erosion processes using the stereophotogrammetric method - Inysheva V.A.; Gusev A.S.; Bronitskaya S.A.; Khomyakova M.A.; Belichev A.A. (BIO Web of Conferences)
Soil is the most important resource on earth, the need for its rational use is fixed in many regulatory and legal sources of the Russian Federation, it is necessary to control the use of land resources, prevent pollution and soil degradation; for these purposes there are measures carried out to monitor the state of the soil cover. All these actions allow for a more rational allocation of funds from the use of land resources, as well as ensure the safety and compliance with environmental standards for the protection of land resources and the environment [2]. This article considers the issue of using three-dimensional models to assess the development of erosion processes on lands suitable for agricultural use, which are a strategic resource. The study of the erosion hazard of lands is of great importance in the modern world, where there is an active change in the natural environment under the influence of human activity. Soil erosion is a serious problem that can lead to the loss of land fertile layer, lower yields, and increased risk of natural disasters. In this regard, the assessment of land erosion hazard is an urgent task that requires an integrated approach and the use of modern methods and technologies [1].